Customer satisfaction on counter service at Majlis Bandaraya Melaka Bersejarah (MBMB) / Nor Shadiah Abdul Rahaman and Noorsuria Abdullah - Abdul Rahaman, Nor Shadiah; Abdullah, Noorsuria (Faculty of Administrative Science and Policy Studies, 2011)
The role of the public sector in shaping the development of the nation has always been extensively debated in the Malaysian parliament but received less attention in the research literature. In the case of local government in Malaysia, their position as the lowest of the three levels in the government hierarchy, they are very close to the public. Local government can be defined as one level of government that exists in the country. Its establishment aims to provide opportunities for local residents to take part in the administration. These institutions have financial autonomy and the right to enact laws relating to jurisdiction and are subject to local government, power under state government. However, the federal government, through the National Council for Local Government and Housing and local government directing authority assist and control the local government in the country. Local government functions provide municipal services in the areas specified. Among these services are public healthcare, public sanitation, and providing solid waste collection system. There are three types of local government in Malaysia which are the City Council, the Municipal Council, and District Council (Dewan Bahasa dan Pustaka, 2011).